Internalized racism and mental health among African-Americans, US-born Caribbean Blacks, and foreign-born Caribbean Blacks. Issue 1 (2nd January 2017) - Mouzon, Dawne M.; McLean, Jamila S.
ABSTRACT: Objectives. The tripartite model of racism includes personally mediated racism, institutionalized racism, and the less-oft studied internalized racism. Internalized racism – or negative beliefs about one's racial group – results from cultural racism that is endemic in American society. In this project, we studied whether these negative stereotypes are associated with mental health among African-Americans and Caribbean Blacks. Design. Using secondary data from the National Survey of American Life, we investigated the association between internalized racism and mental health (measured by depressive symptoms and serious psychological distress (SPD)) among these two groups. We also explored whether ethnicity/nativity and mastery moderate the association between internalized racism and mental health among African-Americans and Caribbean Blacks. Results. Internalized racism was positively associated with depressive symptoms and SPD among all Black subgroups. However, internalized racism was a weaker predictor of SPD among foreign-born Caribbean Blacks than US-born Caribbean Blacks and US-born African-Americans. Additionally, higher mastery was protective against distress associated with internalized racism. Conclusion. Internalized racism is an important yet understudied determinant of mental health among Blacks. Future studies should take into account additional heterogeneity within the Black population (e.g. African-born individuals) and other potential protective mechanisms in addition to mastery (e.g. self-esteem and racial identity).